2016
DOI: 10.1080/21645515.2016.1246094
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of trivalent influenza vaccine in patients with lung cancer undergoing anticancer chemotherapy

Abstract: Lung cancer is a leading cause of cancer-related death, and patients with lung cancer are a priority group for influenza vaccination. However, few studies have assessed the immunogenicity of the influenza vaccine in these patients. Here, we performed a prospective study to evaluate the immunogenicity of the influenza vaccine in patients with lung cancer undergoing anticancer chemotherapy. Twenty-five patients with lung cancer undergoing anticancer chemotherapy and 26 patients with chronic obstructive pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…A recent prospective study to evaluate the immunogenicity of the influenza vaccine in patients with lung cancer undergoing anticancer chemotherapy included 25 patients with lung cancer and 26 patients with chronic obstructive pulmonary disease (COPD) as controls. 78 Lung cancer patients who received trivalent influenza vaccine had post-vaccination seroprotection rates of 84% for both A(H1N1) and A(H3N2), similar to the levels observed in patients with chronic obstructive pulmonary disease, but had significantly lower odds for seroprotection against the B strain. Thus, the response to influenza vaccine may be dependent of the type of influenza strain as well as the type of chemotherapy.…”
Section: Solid Tumours and Hematologic Malignancysupporting
confidence: 52%
“…A recent prospective study to evaluate the immunogenicity of the influenza vaccine in patients with lung cancer undergoing anticancer chemotherapy included 25 patients with lung cancer and 26 patients with chronic obstructive pulmonary disease (COPD) as controls. 78 Lung cancer patients who received trivalent influenza vaccine had post-vaccination seroprotection rates of 84% for both A(H1N1) and A(H3N2), similar to the levels observed in patients with chronic obstructive pulmonary disease, but had significantly lower odds for seroprotection against the B strain. Thus, the response to influenza vaccine may be dependent of the type of influenza strain as well as the type of chemotherapy.…”
Section: Solid Tumours and Hematologic Malignancysupporting
confidence: 52%
“…Available data with other vaccines indicate a lower vaccine immunogenicity and efficacy in immunocompromised patients, such as patients undergoing haemodialysis, solid organ transplant recipients [ 7 , 8 ], patients with cancer or haematological malignancy [ 9 , 10 ] and those with autoimmune inflammatory diseases [ 11 ], hence raising the concern of potentially decreased immunogenicity and effectiveness of COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Among lung cancer patients, patients receiving double-platinum chemotherapy showed lower seroprotection rates than patients receiving single-drug therapy. 35 This study showed that the immune response of the vaccine was weakened in an immunosuppressed individual.…”
Section: The Impact Of Various Cancer Treatments On Vaccinesmentioning
confidence: 87%
“…The immune function of cancer patients is weakened during the cancer treatment; thus, the immunity to the virus is reduced. 34,35 Therefore, vaccination of live attenuated vaccines is not recommended for cancer patients.…”
Section: Vaccines Not Recommended For Cancer Patientsmentioning
confidence: 99%